Predictors of treatment interruption among patients on antiretroviral therapy in Akwa Ibom, Nigeria: outcomes after 12 months. Issue 1 (2nd January 2023) - Akpan, Uduak; Kakanfo, Kunle; Ekele, Oche D.; Ukpong, Kufre; Toyo, Otoyo; Nwaokoro, Pius; James, Ezekiel; Pandey, Satish; Olatubosun, Kolawole; Bateganya, Moses
ABSTRACT: Understanding the characteristics of people living with HIV who interrupt antiretroviral therapy (ART) is critical for designing client-centered services to ensure optimal outcomes. We assessed predictors of treatment interruption in 22 HIV clinics in Nigeria. We reviewed records of HIV-positive patients aged ≥15 years who started ART 1 January and 31 March 2019. We determined treatment status over 12 months as either active, or interrupted treatment (defined as interruption in treatment up to 28 days or longer). Potential predictors were assessed using Cox hazard regression models. Overall, 1185 patients were enrolled on ART, 829 (70%) were female, and median age was 32 years . Retention at 1, 3, 6, 9, and 12 months was 85%, 80%, 76%, 72%, and 68%, respectively. Predictors of treatment interruption were post-secondary education ( p  = 0.04), diagnosis through voluntary counseling and testing ( p  < 0.001), receiving care at low-volume facilities ( p  < 0.001), lack of access to a peer counselor ( p  < 0.001), and residing outside the clinic catchment area ( p  = 0.03). Treatment interruption was common but can be improved by focusing on lower volume health facilities, providing peer support especially to those with higher education, and client-centered HIV services for those who live further from clinics..